2011
DOI: 10.1038/nature10624
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells act as rheostats modulating antiviral T cells

Abstract: Anti-viral T cells are thought to regulate whether hepatitis C virus (HCV) and HIV infections result in viral control, asymptomatic persistence, or severe disease, though the reasons for these different outcomes remain unclear. Recent genetic evidence, however, has indicated a correlation between certain natural killer (NK) cell receptors and progression of both HIV and HCV infection1–3, implying that NK cells are playing a role in these T cell-associated diseases. While direct NK cell-mediated lysis of virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
684
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(755 citation statements)
references
References 35 publications
54
684
5
2
Order By: Relevance
“…Such an adjustment in combination with persisting expression of PD-1 could be of vital importance in chronic infections 64,65 . In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 96%
See 1 more Smart Citation
“…Such an adjustment in combination with persisting expression of PD-1 could be of vital importance in chronic infections 64,65 . In strong support of this concept, it was recently shown that a high dose virus infection, which induced a strong "exhausted" phenotype, protected mice from immunopathology while a lower dose, which failed to induce an "exhausted" phenotype, resulted in substantial pathology 74,77 . Similarly, disrupting the von Hippel-Lindau tumor suppressor (VHL) gene causes overwhelming immunopathology by enforcing cytotoxic activity of T-cells in persisting infections 78 .…”
Section: Pd-1 and Other Inhibitory Receptors Enable A Functional Contmentioning
confidence: 96%
“…Accordingly, the deterioration in the T-cell response following CD4 depletion in chronic infection might be a consequence of losing these memory-like T-cells. Interestingly, a recent publication indicated that the impact of CD4 T-cells on CD8 T-cells in chronic infection could also be controlled by NK cells, which reduce the number of CD4 T-cells and concomitantly the number of CD8 T-cells 74 .…”
Section: Why Are Memory-like Cells Formed In Chronic Infections?mentioning
confidence: 99%
“…Whether memory NK cells limit T cell responses by directly killing activated T cells has not been assessed but should be considered 71 . It is tempting to speculate that, in situations in which T cell memory is impaired, memory NK cells might in part provide protection against disease.…”
Section: Exploiting Nk Cell Memory For Antiviral Therapymentioning
confidence: 99%
“…It has been reported that NK cells regulate T cell responses through multiple direct and indirect mechanisms, including NK cell-mediated killing of activated CD8 + T cells (14,15,(18)(19)(20)(21), CD4 + T cells (18,19,22,23), and also of dendritic cells (DCs) (12,24,25). However, little is known about a possible NK cell-mediated inhibitory/regulatory role during antitumor immune responses.…”
mentioning
confidence: 99%